2020
DOI: 10.1186/s40168-020-00843-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the attenuation of intestinal inflammation and modulation of the gut microbiome by krill oil using in vitro and in vivo models

Abstract: Background: The anti-inflammatory property of ω-3 polyunsaturated fatty acids (PUFA) has been exploited in the management of inflammatory bowel disease (IBD) with promising results. However, it remains unclear if PUFA play a significant role in the resolution of inflammation and promotion of mucosal healing. Krill oil (KO) is a natural product rich in PUFA and the potent antioxidant, astaxanthin. In this study, we attempted to understand the mechanisms through which KO modulates the gut microbiome and metabolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 78 publications
(93 reference statements)
2
71
0
1
Order By: Relevance
“…Evidence is mounting that these metabolic features are microbiome-dependent and contribute to the control of infection and level of inflammation in pigs 16,17 but are also relevant to intestinal inflammation in humans 106,107 . Recent evidence has shown that other dietary components such as omega-3-enriched krill oil can enhance the diversity of the intestinal microbiome and level of inflammation in pigs infected with T. suis 108 . Dietary interventions that modulate metabolic and infectious diseases that are also important in humans have been used successfully in pigs supplemented with defined micro-and macro-nutrients 109,110 , phytonutrients 111 and probiotics 112 as well as more complex food matrices that also effect change in microbiome linked to disease outcome (Solano-Aguilar et al, in review).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is mounting that these metabolic features are microbiome-dependent and contribute to the control of infection and level of inflammation in pigs 16,17 but are also relevant to intestinal inflammation in humans 106,107 . Recent evidence has shown that other dietary components such as omega-3-enriched krill oil can enhance the diversity of the intestinal microbiome and level of inflammation in pigs infected with T. suis 108 . Dietary interventions that modulate metabolic and infectious diseases that are also important in humans have been used successfully in pigs supplemented with defined micro-and macro-nutrients 109,110 , phytonutrients 111 and probiotics 112 as well as more complex food matrices that also effect change in microbiome linked to disease outcome (Solano-Aguilar et al, in review).…”
Section: Discussionmentioning
confidence: 99%
“…We found an increase in the aerobic metabolism module, containing amino acid metabolism (alanine, aspartate and glutamate) and the citrate cycle; this result indicated the potential of the microbial environment to shift toward more aerotolerant conditions ( Table S4 ). We also observed overexpression of histidine metabolism in DKD; its product histamine might be involved in mediating the inflammatory response [ 51 ]. ABC transporters mediate the transport of hydrophilic compounds and promote the growth of various bacteria, such as Mycobacterium tuberculosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amplicons were nally puri ed using Agencourt AMPure XP bead kits (Beckman Coulter Genomics, Danvers, MA). The library pool was sequenced in an Illumina MiSeq sequencer with an Illumina MiSeq Reagent Kit according to a protocol previously described [36].…”
Section: Dna Extraction 16s Rrna Gene Ampli Cation and Sequencingmentioning
confidence: 99%